Odd-order Cayley graphs with commutator subgroup of order psup muqsup nu are hamiltonian - Morris, Dave Witte (Ars mathematica contemporanea, 2015)
We show that if ?$G$? is a nontrivial, finite group of odd order, whose commutator subgroup ?$G, G$? is cyclic of order ?$p^μ q^ν$?, where ?$p$? and ?$q$? are prime, then every connected Cayley graph on ?$G$? has a hamiltonian cycle.
Keywords: Cayley graph; Cayleyjev graf; commutator subgroup; hamiltonian cycle; hamiltonski cikel; komutatorska podgrupa